Argil modified high-temperature ceramic coating material as well as preparation method and application thereof
By modifying high-temperature ceramic coating materials with alumina and silica in clay, the contamination and coking problems caused by sodium boiling in high-temperature boilers are solved, and coating with high hardness, high heat resistance and adhesion is achieved , reduces economic costs and improves security.
Patent Information
- Application Number
- CN202411325360.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-20
AI Technical Summary
When the prior art deals with the contamination and coking problems caused by sodium boiling in high-temperature boilers, traditional cleaning and maintenance methods lead to economic losses and safety hazards. The combination strength of the metal thermal spray coating is low and has a short durability life, which cannot effectively solve the problem of high-temperature corrosion.
Using clay-modified high-temperature ceramic coating materials, including silicates, aluminum nitride, boron nitride, talc, zirconium boride, zirconium oxide, alumina, cerium oxide and clay, the high-temperature ceramic coating materials, including silicates, aluminum nitride, boron nitride, talc, zirconium oxide, cerium oxide and clay, the high-temperature ceramic coating materials are formed by specific mix A coating with hardness, high heat resistance and high adhesion, uses clay alumina and silica to improve acid resistance and chemical stability.
It improves the coating's high temperature and corrosion resistance, slag resistance, high thermal conductivity, high stability and adhesion, extends the service life of the coating, reduces economic costs, and provides safer operating conditions.
Smart Images

Figure CN119161176A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high temperature resistant ceramic coatings, and in particular to a clay-modified high temperature ceramic coating material and a preparation method and application thereof. Background Art
[0002] Sodium has a relatively low boiling point of about 883°C. Therefore, when the sodium in the boiler reaches or exceeds this temperature, it changes to a gas phase, and then when the sodium gas cools to a temperature close to or below its freezing point, it usually induces slagging.
[0003] Traditional treatment methods for contamination and coking problems usually include regular cleaning and maintenance to prevent the accumulation of pollutants and deposits. However, this method may cause the boiler to shut down, causing continuous economic losses and energy waste to the company, and in some cases there are still safety hazards. For the challenge of high-temperature corrosion, metal thermal spraying is usually used in the prior art to enhance the high-temperature corrosion resistance of the furnace wall. However, the bonding strength between the metal thermal spray coating and the substrate is limited, and the coating cracks and falls off to varying degrees during use. In addition, the tolerance in a reducing atmosphere is poor, the coating has a short service life, and the economic cost to the company is high. At present, these problems have not been effectively solved. Summary of the invention
[0004] The purpose of the present invention is to provide a clay-modified high-temperature ceramic coating material and a preparation method and application thereof, introduce clay into the high-temperature resistant ceramic coating material to improve the high-temperature resistance, strength, corrosion resistance, adhesion and other properties of the ceramic coating, so as to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention is to provide a clay-modified high-temperature ceramic coating material, the raw materials of which include silicate, aluminum nitride, boron nitride, talcum powder, zirconium boride, zirconium oxide, aluminum oxide, cerium oxide, clay and water, and the mass percentages of the raw materials of the clay-modified high-temperature ceramic coating material are: 5-10% silicate, 1-5% aluminum nitride, 1-5% boron nitride, 0.1-1% talcum powder, 1-3% zirconium boride, 1-5% zirconium oxide, 1-5% aluminum oxide, 0.1-1% cerium oxide, 0.1-2% clay and 63-90% water; the clay and water are added in the form of a clay dispersion.
[0007] Preferably, the clay is waste incineration residue clay.
[0008] More preferably, the method for preparing the pottery clay comprises the following steps: pyrolyzing the garbage at low temperature, passing through a coarse sieve, washing the sieved material with deionized water for multiple times until it is neutral, washing it with acetic acid, and then washing it again with deionized water until it is neutral, drying it, passing through a fine sieve, and obtaining the pottery clay;
[0009] The low temperature pyrolysis is pyrolysis at 300°C for 3h;
[0010] The coarse screen has a mesh size of 100, and the fine screen has a mesh size of 200.
[0011] The second technical solution of the present invention: provides a method for preparing the above-mentioned clay-modified high-temperature ceramic coating material, comprising the following steps: weighing silicate, aluminum nitride, boron nitride, talcum powder, zirconium boride, zirconium oxide, aluminum oxide, cerium oxide, clay and water according to the required proportions, mixing the above-mentioned raw materials evenly to obtain the clay-modified high-temperature ceramic coating material.
[0012] Preferably, clay and water are first made into a dispersion, and then mixed with other raw materials; the mixing is first ultrasonic dispersion, and then an electric stirrer or an electromagnetic stirrer is used, the stirring rate is 100-800 rpm, and the stirring time is 0.5-5h.
[0013] The third technical solution of the present invention is to provide a high-temperature anti-corrosion ceramic coating, which is obtained by spraying or brushing the above-mentioned clay-modified high-temperature ceramic coating material on a substrate and then drying it.
[0014] Preferably, the thickness of the high temperature anti-corrosion ceramic coating is 80-150 μm.
[0015] The present invention discloses the following technical effects:
[0016] The present invention introduces clay into the high temperature resistant ceramic coating material, and utilizes the characteristics of the components such as the aluminum oxide in the clay having good acid corrosion resistance and being able to resist acidic media such as sulfuric acid and hydrochloric acid, and the silicon dioxide in the clay having high chemical stability and having good resistance to acidic and alkaline environments, thereby comprehensively improving the high temperature resistant ceramic coating material's high temperature corrosion resistance, slag slagging resistance, high thermal conductivity, high wear resistance, high stability and other properties. In addition, the clay powder in the coating can also increase the surface roughness of the coating to provide more physical anchor points, thereby improving adhesion, and the resulting coating has a compact structure and a sealing effect, can isolate the corrosive atmosphere, and is helpful in protecting the substrate.
[0017] The clay-modified high-temperature ceramic coating material provided by the present invention can form a ceramic coating with high hardness, high heat resistance and high adhesion on the substrate, which is one of the important means to achieve high-temperature corrosion protection of metals. The development of this technology has important technical reserves and development prospects for clay application products. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 The main element diagram of the unscreened clay from the waste incineration residue after coarse sieving (100 mesh) and fine sieving (200 mesh);
[0020] Figure 2 These are SEM images of the clay from waste incineration residues used in Examples 1-3 and Comparative Example 1; A and B are SEM images of the clay at different magnifications. DETAILED DESCRIPTION
[0021] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0022] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0023] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0024] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0025] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0026] The method for preparing the waste incineration residue clay used in the following Examples 1-3 and Comparative Example 1 of the present invention is as follows: pyrolyze the domestic waste at 300°C for 3h, pass through a 100-mesh sieve, wash the sieved material with deionized water several times until it is neutral, then wash it with acetic acid until the pH reaches about 4, then wash it with deionized water again until it is neutral, use an oven to dry at 80°C for 5h, take it out and pass through a 200-mesh sieve to obtain the waste incineration residue clay. The components of the obtained clay mainly include single substances and oxides such as Na, Mg, Al, Si, S, Cl, K, Ca, Ti, Cr, Mn, Fe, Co, Ni, Cu, Zn, Br, Rb, Sr, Zr, Ba, Pb, Ce, etc. The waste incineration residue clay prepared from other main domestic wastes can also achieve the technical effect of the present invention.
[0027] The waste incineration clay used in the present invention is a product of harmless treatment of daily carbon-containing solid waste garbage enrichment. Compared with general clay, the clay prepared from garbage enrichment products contains more corrosion-resistant elements and has a smaller particle size, and is more suitable for the preparation of coatings. The waste incineration clay used in the present invention is a product of waste resource utilization. While taking into account the coating performance, it is also more in line with the concept of resource recycling.
[0028] Other raw materials used in the following examples and comparative examples of the present invention can all be purchased from the market.
[0029] Example 1
[0030] 1g of waste incineration residue clay and 68ml of water were mixed and ultrasonically dispersed to obtain a waste incineration residue clay dispersion. 10g of sodium silicate, 5g of aluminum nitride, 3g of boron nitride, 1g of talc, 3g of zirconium boride, 3g of zirconium oxide, 5g of aluminum oxide and 1g of cerium oxide were accurately weighed and added to the waste incineration residue clay dispersion in sequence, firstly ultrasonically dispersed, and then stirred at a rate of 100rpm for 30min using an electric stirrer to obtain a clay-modified high-temperature ceramic coating material.
[0031] Example 2
[0032] 2g of waste incineration residue clay and 67ml of water were mixed and ultrasonically dispersed to obtain a waste incineration residue clay dispersion. 10g of sodium silicate, 5g of aluminum nitride, 3g of boron nitride, 1g of talc, 3g of zirconium boride, 3g of zirconium oxide, 5g of aluminum oxide and 1g of cerium oxide were accurately weighed and added to the waste incineration residue clay dispersion in sequence, first ultrasonically dispersed, and then stirred at a rate of 100rpm for 30min using an electric stirrer to obtain a clay-modified high-temperature ceramic coating material.
[0033] Example 3
[0034] 3g of waste incineration residue clay and 66ml of water were mixed and ultrasonically dispersed to obtain a waste incineration residue clay dispersion. 10g of sodium silicate, 5g of aluminum nitride, 3g of boron nitride, 1g of talc, 3g of zirconium boride, 3g of zirconium oxide, 5g of aluminum oxide and 1g of cerium oxide were accurately weighed and added to the waste incineration residue clay dispersion in sequence, first ultrasonically dispersed, and then stirred at a rate of 100rpm for 30min using an electric stirrer to obtain a clay-modified high-temperature ceramic coating material.
[0035] Comparative Example 1
[0036] 10g of waste incineration residue clay and 59ml of water were mixed and ultrasonically dispersed to obtain a waste incineration residue clay dispersion. 10g of sodium silicate, 5g of aluminum nitride, 3g of boron nitride, 1g of talc, 3g of zirconium boride, 3g of zirconium oxide, 5g of aluminum oxide and 1g of cerium oxide were accurately weighed and added to the waste incineration residue clay dispersion in sequence, first ultrasonically dispersed, and then stirred at a rate of 100rpm for 30min using an electric stirrer to obtain a clay-modified high-temperature ceramic coating material.
[0037] Comparative Example 2
[0038] Accurately weigh 10 g of sodium silicate, 5 g of aluminum nitride, 3 g of boron nitride, 1 g of talc, 3 g of zirconium boride, 3 g of zirconium oxide, 5 g of aluminum oxide, 1 g of cerium oxide and 71 ml of water, first disperse them by ultrasonication, and then use an electric stirrer to stir at a rate of 100 rpm for 30 minutes to obtain a ceramic coating material.
[0039] The coating materials obtained in Examples 1-3 and Comparative Examples 1-2 were filtered through a 200-mesh screen and poured into a sprayer. The spraying distance was 50 cm and the spraying amount was 200 g / m 2 , spray evenly on the pipe, place the pipe in a vacuum drying oven at 100°C for 20 minutes and then take it out, so that a coating is formed on the surface of the pipe. The performance tests are conducted on the pipes sprayed with the coating materials obtained in Examples 1-3 and Comparative Examples 1-2, respectively, and the specific test methods are as follows:
[0040] The test of its hemispherical emissivity (blackness) refers to "GB / T 25261-2018 Reflective insulation coating for construction", the thermal conductivity refers to "GBT 39862-2021 Test of thermal conductivity of high thermal conductivity ceramics", the adhesion refers to "GB T 5210-2006 Adhesion test of paint and varnish by pull-off method", the hardness test refers to "GBT 6739-2006 Determination of paint film hardness by pencil method for paint and varnish", the heat resistance (1600℃, 100h) refers to "GBT 1735-2009 Determination of heat resistance of paint and varnish", the wear resistance refers to "GB T 23988-2009 Determination of wear resistance of coatings by falling sand method", the thermal shock resistance refers to "GB / T 37246-2018 Test method for thermal shock resistance of fine ceramics", the thermal expansion coefficient determination refers to "GB / T 16535-2008 Test method for thermal expansion coefficient of fine ceramics - push rod method", salt spray resistance determination reference "GB / T 10125-2021 Artificial atmosphere corrosion test salt spray test", coating thickness measurement reference "GB / T 13452.2-2008 Paint and varnish film thickness determination standard", etc., and scanning electron microscopy analysis was performed on the coating after salt spray corrosion.
[0041] High temperature molten salt resistance test of coating: 20g of KCl and Na2SO4 were mixed in a mortar at a mass ratio of 19:1, ground and mixed evenly, and then put into a crucible. The tube (coating surface) sprayed with the coating material obtained in Example 1-3 and Comparative Example 1-2 was covered downward on the crucible, and molten salt vapor corrosion was carried out at 600°C for 8h to observe whether the coating rusted and fell off. The test results of Examples 1-3 and Comparative Examples 1-2 are shown in Table 1.
[0042] Table 1 Test results of coating properties
[0043]
[0044] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A clay-modified high-temperature ceramic coating material, characterized in that: The raw materials include silicate, aluminum nitride, boron nitride, talc, zirconium boride, zirconium oxide, aluminum oxide, cerium oxide, clay and water. The mass percentage of each raw material of the clay-modified high-temperature ceramic coating material is: The clay and water are added in the form of a clay dispersion.
2. The clay-modified high-temperature ceramic coating material according to claim 1, characterized in that: The pottery clay is waste incineration residue pottery clay.
3. The clay-modified high-temperature ceramic coating material according to claim 2, characterized in that: The method for preparing the pottery clay comprises the following steps: pyrolyzing the garbage at low temperature, passing through a coarse sieve, washing the sieved material with deionized water for multiple times until it is neutral, washing it with acetic acid, and then washing it again with deionized water until it is neutral, drying it, passing through a fine sieve, and obtaining the pottery clay.
4. The clay-modified high-temperature ceramic coating material according to claim 3, characterized in that: The low temperature pyrolysis is pyrolysis at 300° C. for 3 h.
5. The clay-modified high-temperature ceramic coating material according to claim 3, characterized in that: The coarse screen has a mesh size of 100, and the fine screen has a mesh size of 200.
6. A method for preparing the clay-modified high-temperature ceramic coating material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Silicate, aluminum nitride, boron nitride, talc, zirconium boride, zirconium oxide, aluminum oxide, cerium oxide, clay and water are weighed according to required proportions, and the raw materials are evenly mixed to obtain a clay-modified high-temperature ceramic coating material.
7. The method for preparing the clay-modified high-temperature ceramic coating material according to claim 6, characterized in that: First, clay and water are made into a dispersion and then mixed with other raw materials.
8. The method for preparing the clay-modified high-temperature ceramic coating material according to claim 6, characterized in that: The mixing is firstly ultrasonically dispersed, and then an electric stirrer or an electromagnetic stirrer is used, with a stirring rate of 100-800 rpm and a stirring time of 0.5-5 h.
9. A high temperature anti-corrosion ceramic coating, characterized in that: The high-temperature anti-corrosion ceramic coating is obtained by spraying or brushing the clay-modified high-temperature ceramic coating material according to any one of claims 1 to 5 on a substrate and then drying it.
10. The high temperature anti-corrosion ceramic coating according to claim 9, characterized in that: The thickness of the high temperature anti-corrosion ceramic coating is 80-150 μm.
Citation Information
Patent Citations
Waterproof coating
CN102702967A
Environment-friendly building material ceramic product coating
CN103524145A
Household garbage disposal technology
CN107971321A
Environment-friendly fireproof coating and preparation method thereof
CN117024998A
Phosphoric acid-containing graphene oxide modified high-temperature anti-corrosion ceramic coating material and high-temperature anti-corrosion ceramic coating
CN117819953A
